Earthquake loss assessment of steel moment-resisting frames designed according to Eurocode 8. Issue 124 (September 2019) - Macedo, L.; Castro, J.M.
Abstract: Current design and assessment guidelines define several seismic performance levels, aiming to ensure that structures exhibit adequate behaviour at different seismic intensity levels. Typically, the acceptance criteria at different performance levels are met by ensuring that local deformation demands are lower than pre-defined capacities. Despite the proven effectiveness of such an approach, it provides an ambiguous measure of the performance of the building, which, in most cases, is neither meaningful nor appropriate for building owners, stakeholders or decision-makers. The main objective of the research presented in this paper is to evaluate the expected direct economic seismic losses of steel moment-resisting frame structures designed according to Eurocode 8 (EC8). A set of 120 archetype buildings, representative of the current building stock in Portugal, were designed according to Part 1 of EC8 using three different behaviour factors, q : a) code-prescribed upper bound limits for medium and high ductility classes; b) behaviour factor defined according to an Improved Force-Based Design (IFBD) procedure. The PEER-PBEE methodology with the improvements proposed by Ramirez and Miranda [1] was employed for the estimation of expected seismic losses evaluated for the seismic intensity levels considered in Part 3 of EC8. The results obtained indicate that the buildings designed in accordance with EC8 comply with the non-collapse criteria. However, the level of damage could imply significant repair costs. Importantly, the results also highlight that a rational selection of the behaviour factor can result in a reduction of steel weight but still ensuring acceptable levels of expected annual losses. Highlights: A study concerning the evaluation of seismic losses of steel moment frames designed in accordance EC8 is presented. The PEER-PBEE methodology procedure with the improvements proposed by Ramirez and Miranda was used to evaluate a set of 360 steel MRF archetypes. All the studied archetypes comply with the non-collapse criteria defined in EC8 for the design intensity level. However, the level of damage could imply repair costs of around 30% of the building replacement value.